1997
DOI: 10.1046/j.1365-4362.1997.00177.x
|View full text |Cite
|
Sign up to set email alerts
|

Head louse infestations: epidemiologic survey and treatment evaluation in Argentinian schoolchildren

Abstract: The model of research plus action adopted allows the following conclusions to be drawn: (i) individual and isolated treatments for pediculosis are useful, but will not by themselves allow for the epidemiologic control of this parasitosis; (ii) massive, complete, and simultaneous treatments lead to a significant decrease in infestation prevalence; (iii) educational measures tending to foster collective awareness enable greater epidemiologic surveillance to be achieved; (iv) careful inspection of the entire scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 11 publications
0
36
1
Order By: Relevance
“…10% [6,7,8]. During the same period, a high prevalence of head pediculosis was reported in some environments in Asia (85%) [9], South America (81.5%) [10], and Africa (64.1%) [11]. The literature provides scarce data from long-term monitoring of the prevalence of Pediculus humanus capitis invasions in the same environments, which makes it impossible to assess changes in the dynamics of infestation in children and determine the effect of factors contributing to the spread of the parasite in a long-term scale.…”
Section: Discussionmentioning
confidence: 99%
“…10% [6,7,8]. During the same period, a high prevalence of head pediculosis was reported in some environments in Asia (85%) [9], South America (81.5%) [10], and Africa (64.1%) [11]. The literature provides scarce data from long-term monitoring of the prevalence of Pediculus humanus capitis invasions in the same environments, which makes it impossible to assess changes in the dynamics of infestation in children and determine the effect of factors contributing to the spread of the parasite in a long-term scale.…”
Section: Discussionmentioning
confidence: 99%
“…However, the finding of both low and high rates of head lice prevalence in children from countries with different levels of social-economical development indicates that this factor also can present different degrees of importance in head lice distribution in some regions (Hoffmann 1983, Chouela et al 1997. This is partially due to the existence of many factors influencing its prevalence (Arene & Ukaulor 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Head lice are a public health problem in various parts of the world (Ewasechko 1981, Kwaku-Kpikpi 1982, Courtiade et al 1993, Chouela et al 1997, including in Brazil (Linardi et al 1989, Madureira 1991 and may be found in people of all ages. However, school age children are more likely to be infested (Buxton 1938, Lolió et al 1975, Donaldson 1976, Gbakima 1992.…”
mentioning
confidence: 99%
“…Head lice infestation and biting may lead to difficulties such as inflammation, eczema, excoriations, exudations, restlessness, impaired sleeping, slight to intense fever, and swelling of lymph nodes in the neck (Mehlhorn and Aspöck 2008). Survey on the people who have received prior treatment reveals that periodic treatment is ineffective for the control of pediculosis and long-term follow-up is necessary (Chouela et al 1997).…”
Section: Introductionmentioning
confidence: 99%